Pelatihan Peningkatan Ketrampilan Penyusunan Laporan Keuangan Untuk Koperasi Serba Usaha (KSU) SEMESTA - Suripto, Suripto; Prasetya, Victor; Hartoyo, Hartoyo (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of the Community Service activity is to increase the knowledge and understanding of the management and members of the Koperasi Serba Usaha (KSU) "SEMESTA" in Bojongnangka Village, Pemalang about the preparation of cooperative financial statements in accordance with SAK ETAP carried out on 19 March 2023, because based on discussions with the management of KSU Semesta, it shows that the cooperative management has problems in understanding and preparing financial reports. For the training, lecture, tutorial, and discussion techniques were used, discussing the steps in preparing financial statements, the tools needed to prepare financial statements, and practice cases In conclusion, the training activities went smoothly. Participants were enthusiastic by immediately asking questions, and there were several participants who were interested in learning more about cooperative bookkeeping for the smooth running and development of their cooperatives.